ANALISIS ENABLING FACTOR TERHADAP KEJADIAN DIARE PADA BALITA DI WILAYAH PUSKESMAS AIR PUTIH SAMARINDA - Sumadi, Sumadi; Rosdiana, Rosdiana; Istiarto, Istiarto; Rismayanti, Rismayanti (Jurnal Kesehatan, 2025)
Diarrhea is still a problem that always exists in society, especially toddlers because toddlers have immune systems that are still susceptible to diarrhea compared to adults. This study aims to analyze supporting factors, namely facilities and infrastructure for the incidence of toddler diarrhea in the Air Putih Samarinda Health Center work area. The method used is qualitative with the Action Research (AR) approach. Data collection techniques include in-depth interviews with purposive sampling, observation, and documentation. The results of the study to 6 informants were given a pre-test intervention (X01) initial conditions on supporting factors including facilities and infrastructure, each informant had 1 informant who met the requirements and 5 informants who did not meet the requirements. Furthermore, the provision of (X) intervention/treatment which began with an explanation of the contents of the leaflet, then the leaflet was given to the informant. At the time of the post-test (X02) the final condition of the facilities and infrastructure in the 3 stages, showed changes related to facilities and infrastructure that met the requirements as many as 3 informants and some did not meet the requirements as many as 3 informants from the initial condition. It can be concluded that supporting factors, namely facilities and infrastructure, influence the incidence of diarrhea in the work area of ​​the Air Putih Health Center, Samarinda City.